Clinical characteristics and outcomes of surgical resection for brain metastases from lung adenocarcinoma - Li, Ming; Li, Zhiying; Zhang, Hang; Wakimoto, Hiroaki; Sun, Linlin; Wang, Tiantian; Zhou, Shengli; Zhou, Liyun (Frontiers in Oncology, 2025)
ObjectiveThe purpose of this study was to explore the clinical characteristics, survival time and prognostic factors of patients undergoing craniotomy for brain metastases (BM) from lung adenocarcinoma (LUAD).MethodsA total of 208 patients with BM from LUAD who underwent craniotomy at the Zhengzhou University People’s Hospital, Henan province, China from March 2005 to October 2022 were included in this retrospective study. All patients were confirmed as BM of LUAD by histopathology. The clinical data included patient gender, age, occupation, family history of tumor, smoking history, alcohol drinking history, neurological symptoms, history of lung cancer treatment, tumor location, tumor number, tumor size, gene status, expression of S-100, CEA, Ki67, and PD-L1 by immunohistochemistry, KPS after craniotomy, whether tumor therapy was continued after craniotomy, and survival time. Univariate and multivariate Cox regression was used to analyze the prognostic factors of patients undergoing craniotomy for LUAD BM.ResultsA total of 208 patients met the inclusion and exclusion criteria, including 110 males (52.9%) and 98 females (47.1%), with an average age of 61.4 years. 203 patients (97.6%) had neurological symptoms. 84 patients (40.4%) had smoking history, 89 patients (42.8%) had alcohol drinking history, and 31 patients (14.9%) had the family history of tumor. Only 5 patients (2.4%) had received lung cancer treatment before craniotomy. The intracranial location of BM was mostly in the frontal lobe (54, 26.0%) and the metastatic sites were mostly single (117, 56.3%); the metastatic tumor size was mostly between 2-5 cm (141, 67.8%). Genetically, 43.3% patients (90 cases) had EGFR mutations, and immunohistochemical analysis showed that most patients were PD-L1 positive (160, 76.9%) and Ki67 > 30% (137, 65.9%). Most patients (145, 69.7%) had KPS score under 80 after craniotomy. Only 72 patients (34.7%) received continued tumor therapy after craniotomy. 190 patients (91.3%) were successfully followed up. The median survival time was 11.5 months, and the 3-year survival rate was 15.7%. Multivariate analysis revealed that smoking history, Ki67 percentage, KPS after craniotomy, and molecular targeted therapy after craniotomy were independent factors affecting the survival time of patients.ConclusionsAlthough survival remains poor, patients who had no-smoking history, Ki67 percentage ≤30%, KPS≥80 after craniotomy, and molecular targeted therapy after craniotomy can improve the prognosis and prolong the survival time.